2016
DOI: 10.1088/1367-2630/18/4/045022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement-device-independent quantification of entanglement for given Hilbert space dimension

Abstract: We address the question of how much entanglement can be certified from the observed correlations and the knowledge of the Hilbert space dimension of the measured systems. We focus on the case in which both systems are known to be qubits. For several correlations (though not for all), one can certify the same amount of entanglement as with state tomography, but with fewer assumptions, since nothing is assumed about the measurements. We also present security proofs of quantum key distribution (QKD) without any a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…In [23] it was first shown that the Shor-Preskill rate still holds if no correlations are observed in the mismatched bases cases assuming that Alice performs unknown projective qubit measurements. A similar result was recovered numerically in [24] for general qubit POVMs on Alice's side, assuming that Bob also performs qubit measurements. The prepare-and-measure version of BB84 was also studied numerically in [25] at a similar level of device independence, where Alice's source prepares unknown pure qubit states and Bob performs unknown projective qubit measurements.…”
Section: Bb84 and Device Independencesupporting
confidence: 69%
“…In [23] it was first shown that the Shor-Preskill rate still holds if no correlations are observed in the mismatched bases cases assuming that Alice performs unknown projective qubit measurements. A similar result was recovered numerically in [24] for general qubit POVMs on Alice's side, assuming that Bob also performs qubit measurements. The prepare-and-measure version of BB84 was also studied numerically in [25] at a similar level of device independence, where Alice's source prepares unknown pure qubit states and Bob performs unknown projective qubit measurements.…”
Section: Bb84 and Device Independencesupporting
confidence: 69%
“…Among the results presented in this issue, [35] study a 'semi-device-independent' (SDI) model in which one of the devices is trusted; in this scenario they provide improved quantitative bounds for the problem of selftesting an EPR pair, with an analysis based on the phenomenon of EPR steering. [12] considers another SDI model, one in which only the dimension of the system is known but not the measurements, and provides tools to quantify entanglement and security proofs for QKD. [40] studies the security of BB84 under the even weaker assumption that the dimension of only one of the systems is constrained to be a qubit.…”
mentioning
confidence: 99%
“…In Example 2 we have considered a 2 ⊗ 2 separable mixed state (41) having both nonzero Alice to Bob and non-zero Bob to Alice discord. We have shown that the correlation (42) produced by performing some particular local noncommuting measurements on this state can be simulated with LHV-LHS model with random variable having minimum dimension 3.…”
Section: Quantumness As Captured By Super-unsteerabilitymentioning
confidence: 99%
“…This implies that the correlation (42) cannot be simulated by classical-quantum state with dimension 2 ⊗ 2. Hence, the super-unsteerable correlation (42) certifies quantumness of certain 2 ⊗ 2 dimensional resources producing it and provides operational characterization of quantumness of the state (41).…”
Section: Quantumness As Captured By Super-unsteerabilitymentioning
confidence: 99%